Evaluation Framework on Start-up Incubator Business Model: What to Ask and How to Employ Data Management Tools (N-Vivo) - Tifa Noer Amelia (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2020)
In recent years, developing economies countries such as Indonesia witnessing the growth of the incubator business for digital start-ups. Digital start-up is an early-stage business that requires to maintain its growth supported by the ecosystem. One of a prominent part in the ecosystem is a business incubator. This is descriptive research that aims to construct research question guideline and how to organize the gathered data using tools called Nvivo based on the provided evaluation framework.